Distal Tibia Apex Posterior Angulation: A Normal Anatomic Variant with Side-To-Side Symmetry. Issue 4 (November 2022) - Megerian, Mark F.; Schimizzi, Gregory V.; Barth, Kathryn A.; LaValva, Scott; Klinger, Craig E.; Dziadosz, Daniel; Ricci, William M.; Campbell, Sean
Category: Trauma; Ankle Introduction/Purpose: The native sagittal plane alignment of the distal tibia has not been well-described and has implications during the fixation of tibia fractures. Cavovarus foot alignment has been previously thought to influence gastrocsoleus tightness and the potential for anterior talar escape in the setting of an osseous injury in this region. However, the relationship between midfoot alignment and sagittal distal tibia morphology is undescribed. Characterization of this osseous anatomy may be helpful to achieve adequate sagittal alignment during the reduction of distal tibia fractures. The purpose of this study was primarily to characterize distal tibia sagittal morphology and ankle radiographic parameters, determine whether symmetry exists from side-to- side, and secondarily to identify any differences based on midfoot alignment. Methods: 112 patients (60 females, mean age 45.8 years) with bilateral lateral weight-bearing ankle radiographs were retrospectively evaluated (224 ankles). Midfoot morphology was classified as normal, planus, or cavus using Meary's angle (MA) (Planus: MA <-4°, Normal: MA -4°≤x≤4°, Cavus: MA>4°). The angle between the proximal diaphyseal (Line 1) and distal tibia (Line 2) axes was measured, and the location of the center of rotation of angulation (CORA) relative to the plafond was recorded (Figure 1). The horizontal distance (via a line parallel to the floor) from the distal tibia axis (Line 2) to the lateral talar process was measured, as well as the anterior distal tibial angle, and the plafond radius of curvature (ROC). Bilateral ankles and midfoot morphologies were compared using a Mann-Whitney U test and ANOVA, respectively. Correlation was assessed using linear regression. Results: The average distal tibia had 2° of apex posterior angulation with the CORA located 8.0 cm proximal to the plafond. There was no difference by laterality in magnitude of the angulation (p=.358) or distance from the plafond to the CORA (p=.901). The angulation increased as foot alignment transitioned from cavus (1.25°), to normal (1.89°), to planus (3.05°) alignment (r=.32; R2=.102; p<.001). The angulation was larger in men (2.8°) than in women (1.4°) (p<.001) and decreased with increasing patient age (r=.279, R2=.078, p<.001). The lateral talar process was on average 5.9 mm anterior to the distal tibia axis (Line 2), more anterior with cavus versus planus alignment (6.7mm vs. 4.8mm) (p<.001). The average anterior distal tibial angle and plafond ROC were 83.6° and 22.9 mm, respectively, with no significant differences by laterality or midfoot morphology (p>.05 for both). Conclusion: The distal tibia has a consistent apex posterior bow that is symmetric from side-to-side, but variable from patient- to-patient. Distal tibia osseous morphology is related to midfoot alignment, sex, and age. Cavus alignment is additionally correlated with anterior translation of the lateral talar process relative to the distal tibia axis. Surgeons treating distal tibia fractures may consider the use of contralateral imaging as a reduction template to help restore patient-specific sagittal alignment. A tibial nail that ends anterior in the distal segment of a distal tibia fracture should prompt the surgeon to carefully evaluate whether sagittal alignment has been restored.